Long-Term Changes in the Water Mass Properties in the Balearic Channels Over the Period 1996–2019 - Vargas-Yáñez, Manuel; Juza, Mélanie; García-Martínez, M. Carmen; Moya, Francina; Balbín, Rosa; Ballesteros, Enrique; Muñoz, María; Tel, Elena; Pascual, Josep; Vélez-Belchí, Pedro; Salat, Jordi (Frontiers in Marine Science, 2021)
The analysis of a 24-year time series of CTD casts collected in the Balearic Channels (1996-2019) has allowed detecting and quantifying long-term changes in water mass properties in the Western Mediterranean. For the complete period of time, the intermediate waters have experienced a warming and salting at rates of 1.4 ºC/100 yr and 0.3-0.6 /100 yr for the Western Intermediate Water, and 1ºC/100 yr and 0.3-0.4 /100 yr for the Levantine Intermediate Water. The density of these two water masses has not changed. The deep waters, defined as those denser than 29.1 kg/m3, showed positive trends in temperature, salinity and density (0.8ºC/100 yr, 0.2 /100 yr and 0.02 kg.m-3/100 yr, respectively). The high temporal variability of the upper layer makes the detection of long-term changes more difficult. Nevertheless, combining the CTD data with temperature data from the oceanographic station at L'Estartit and simulated data from the NCEP/NCAR reanalysis, it can be established that the Atlantic Water increased its temperature at a rate of 2.1-2.8 ºC/100 yr and likely its salinity at a rate of 0.6 /100 yr. The water column absorbed heat at a rate equivalent to 1-1.2 W/m2. All these trends are much higher than those reported in previous works. Besides these changes, other alterations related to the Western Mediterranean Transition, have been observed over shorter periods of time. The temperature and salinity of the intermediate waters increased before the winter 2004/05 and then the temperature and salinity of deep waters increased dramatically in 2005. The density of the deep water reached values unprecedented before 2005. Deep and intermediate waters were uplifted by the presence of such dense deep waters. The arrival of warmer and saltier intermediate waters from the Eastern Mediterranean is also observed, mainly after 2010.